1998
DOI: 10.1037/0012-1649.34.4.662
|View full text |Cite
|
Sign up to set email alerts
|

A cross-national study of self-evaluations and attributions in parenting: Argentina, Belgium, France, Israel, Italy, Japan, and the United States.

Abstract: This study investigated and compared ideas about parenting in Argentine, Belgian, French, Israeli, Italian, Japanese, and U.S. mothers of 20-month-olds. Mothers evaluated their competence, satisfaction, investment, and role balance in parenting and rated attributions of successes and failures in 7 parenting tasks to their own ability, effort, or mood, to difficulty of the task, or to child behavior. Few cross-cultural similarities emerged; rather, systematic culture effects for both self-evaluations and attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
127
2
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(158 citation statements)
references
References 46 publications
20
127
2
3
Order By: Relevance
“…Os escores relativos à desejabilidade social obtidos neste estudo (M = 17,8, DP = 4,57) mostraram-se muito semelhantes aos relatados em outros estudos 12,24 . As mães não apresentaram níveis de desejabilidade social superiores aos observados em outros estudos semelhantes ou que pudessem pôr em dúvida, sob esse aspecto, os resultados do estudo.…”
Section: Resultsunclassified
“…Os escores relativos à desejabilidade social obtidos neste estudo (M = 17,8, DP = 4,57) mostraram-se muito semelhantes aos relatados em outros estudos 12,24 . As mães não apresentaram níveis de desejabilidade social superiores aos observados em outros estudos semelhantes ou que pudessem pôr em dúvida, sob esse aspecto, os resultados do estudo.…”
Section: Resultsunclassified
“…However, a cross-national study reported that Japanese mothers rated themselves less competent and satisfied in their parenting, although they were high in investment when compared to women in six European, South and North American countries [1]. Likewise, an international comparison survey conducted by the Japanese government reported that the proportion of mothers who considered raising children enjoyable was 44% among Japanese mothers, while the number was 81% in the United States [2].…”
Section: Introductionmentioning
confidence: 99%
“…), and infants were more enmeshed in a dense social setting (Bornstein, 1995;New and Richman, 1996). Bornstein et al (1998), on the basis such findings, summarized the 'Italian way' as: 'In the traditional view, parenting per se is not thought to exert direct effects on child growth and development, mothers actively discourage early self-actualization skills, and mothers hold later expectations for children's developmental accomplishments. ' (p. 663).…”
Section: Cultural Influencesmentioning
confidence: 96%